An intraaortic solution trial to prevent spinal cord injury in a rabbit model - Tetik, Ö; Islamoglu, F; Yagdi, T; Atay, Y; Çalkavur, T; Özbek, C; Vüksel, M (W B Saunders Co Ltd, 2001)
Objectives: to evaluate the effectiveness of an intraaortic delivered solution on preventing spinal cord injury. Design:forty rabbits were allocated into five equal groups. Materials and Methods: one clamp was placed just distal to the left renal artery, and another was placed just above the iliac bifurcation for 40 min. Group I was not infused (control group). Through a 24G vascular catheter inserted into the isolated aortic segment, 20 nd of LR solution at room temperature (Group 2) 20 ml of LR solution at 3 degreesC (Group 3), and 20 ml of LR solution at 3 degreesC containing 30 mg/kg of methylprednisolone (Group 4) were infused over 3 min. In Group 5, 10mg/kg of vitamins E and C were delivered two days before the experiment, and 20ml of LR solution at 3 degreesC containing 30 mg/kg of methylprednisolone, and 10 mg/kg of vitamins E and C was infused at the operation. Postoperative spinal cord function was assessed using Tarlov's criteria. Results: the neurologic status of Groups 3, 4, and 5 was significantly superior to that of Groups I and 2. No paraplegia was observed in Groups 4 and 5. Spastic paraplegia occurred in all rabbits of Groups I and 2, and in 20% of Group 3. In the electron microscopic evaluation of spinal cord specimens, normal histologic structure was observed in Groups 4 and 5, whereas, some derangements were observed in all others. Conclusions: intraaortic infusion of a hypothermic blended solution containing methylprednisolone, vitamins C and E provided best protection against postischaemic spinal cord dysfunction.
49th International Congress of the European-Society-for-Cardiovascular-Surgery -- JUN 24-27, 2000 -- Dresden, GERMANY
Keywords: spinal cord protection; paraplegia; ischaemic injury